Interactive E-Module Development through Chemistry Magazine on Kvisoft Flipbook Maker Application for Chemistry Learning in Second Semester at Second Grade Senior High School - Roza Linda; H Herdini; Ika Sulistya S; Teja Pratama Putra (Universitas Pendidikan Indonesia, 2018)
This research is an innovative development on teaching materials in order to intensify the movement of